Shelley in the Transition to Russian Symbolism: Three Versions of 'Ozymandias' - Wells, David (Modern Humanities Research Association, 2013)
One of the features of the early Russian Symbolist movement in the 1890s is its appropriation of literary models previously championed by the civic tradition which preceded it and to which it was both philosophically and aesthetically opposed. One example can be found in treatments of the English poet Percy Bysshe Shelley. This article compares civic and Symbolist translations of Shelley’s sonnet ‘Ozymandias’, showing that the same material could be used to support radically different views, and that the literary world of the period was a particularly fluid space in which multiple overlapping trends competed for the attention of readers.